2015
DOI: 10.1177/1745691615568999
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness Across the Life Span

Abstract: Most people have experienced loneliness and have been able to overcome it to reconnect with other people. In the current review, we provide a life-span perspective on one component of the evolutionary theory of loneliness—a component we refer to as the reaffiliation motive (RAM). The RAM represents the motivation to reconnect with others that is triggered by perceived social isolation. Loneliness is often a transient experience because the RAM leads to reconnection, but sometimes this motivation can fail, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
676
3
17

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 680 publications
(730 citation statements)
references
References 97 publications
(170 reference statements)
34
676
3
17
Order By: Relevance
“…In line with this, research could further explore whether the presence of a friend or family member in contexts with nonintimate company could buffer the negative effects of nonintimate company. As previous research has shown that lonely individuals are hypersensitive to negative social cues (see, e.g., Qualter et al, 2015), lonely adolescents may also need to learn adaptive coping strategies to deal with relatively negative social environments, such as nonintimate company.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, research could further explore whether the presence of a friend or family member in contexts with nonintimate company could buffer the negative effects of nonintimate company. As previous research has shown that lonely individuals are hypersensitive to negative social cues (see, e.g., Qualter et al, 2015), lonely adolescents may also need to learn adaptive coping strategies to deal with relatively negative social environments, such as nonintimate company.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a review of the ontogeny of loneliness has differentiated between environmental triggers of loneliness across the life span (Qualter et al 2015). It was suggested that as of adolescence, romantic relationships become increasingly important, and that compromised quality of that type of relationship is mostly related to loneliness.…”
Section: Lonelinessmentioning
confidence: 99%
“…Similarly, marital quality and life partnership fulfill needs for belonging in old age. However, at this stage of life these needs are challenged as widowhood, illness, and reduced social activities become sources of loneliness (Qualter et al 2015).…”
Section: Lonelinessmentioning
confidence: 99%
“…Loneliness is a common phenomenon associated with old age due to changes in the quality and quantity of social relationships (Luanaigh & Lawlor, 2008;Qualter et al, 2015). Consequently, elderly people may experience feelings of distress, loss and unmet social needs (Hawkley & Cacioppo, 2010).…”
Section: Introductionmentioning
confidence: 99%